Hubungan Tingkat Kecukupan Zat Gizi Makro, Status Gizi dan Aktivitas Fisik Terhadap Kebugaran Atlet Bulutangkis di PB Jaya Raya Ragunan Jakarta - Suciana, Aulya Marthadina Suciana; Nazhif Gifari; Laras Sitoayu; Rachmanida Nuzrina; Dudung Angkasa (JURNAL GIZI DAN KESEHATAN, 2021)
An athlete is required to always maintain his physical fitness. Fitness is one indicator in determining a person's health, especially for an athlete. The fitter a person is, the healthier that person will be. This study aims to analyze the relationship between the level of macro nutrient adequacy, nutritional status and physical activity on the badminton athletes in PB Jaya Raya club. This study used a quantitative research design with a cross sectional study design and a sample of 32 athletes. Data obtained through online google form, namely data on carbohydrate, protein, fat intake with a 3x24 hour food record, nutritional status with BMI/U and Physical activity using the IPAQ questionnaire sheet. Data analysis used the Spearman Rank Correlation Test. As many as 28 (87.5%) of respondents had insufficient levels of carbohydrate adequacy, and as many as 31 (96.9%) of respondents had a higher level of protein sufficiency as well as an adequate level of fat 31 (96.9%) of respondents had sufficient levels of sufficiency of excess fat. It is known that 19 (59.4%) respondents have a moderate level of physical activity. And it is known that as many as 25 (78.1%) respondents are fit. There was no significant relationship between all research variables (p≥0,05). The conclusion of this study shows that there is no relationship between the level of carbohydrate adequacy, protein adequacy level, fat adequacy level, nutritional status and physical activity on athletes fitness (p≥0,05). There is no significant relationship between the adequacy level of macro nutrients, nutritional status and physical activity on the fitness of badminton athletes. Abstrak Seorang atlet dituntut untuk selalu menjaga kebugaran jasmaninya. Kebugaran adalah salah satu indikator untuk menentukan derajat kesehatan seseorang, terutama untuk seorang atlet. Semakin bugar seseorang maka semakin sehat juga orang tersebut. Penelitian ini bertujuan menganalisis hubungan tingkat kecukupan zat gizi makro, status gizi dan aktivitas fisik terhadap kebugaran pada atlet bulutangkis yang berada di klub PB Jaya Raya. Penelitian ini menggunakan jenis penelitian kuantitatif dengan desain penelitian cross sectional dan sampel berjumlah 32 atlet. Data diperoleh melalui online google form yaitu data asupan karbohidrat, protein, lemak dengan food record 3x24 jam, status gizi dengan IMT/U dan aktivitas fisik dengan lembar kuesioner IPAQ. Analisis data menggunakan uji Korelasi Rank Spearman. Sebanyak 28 (87,5%) responden memiliki tingkat kecukupan karbohidrat yang kurang, serta sebanyak 31 (96,9%) responden memiliki tingkat kecukupan protein yang lebih begitu pun dengan tingkat kecukupan lemak 31 (96,9%) responden memiliki tingkat kecukupan lemak yang berlebih. Diketahui sebanyak 19 (59,4%) responden memiliki tingkat aktivitas fisik sedang. Serta diketahui bahwa sebanyak 25 (78,1%) responden bugar. Tidak ada hubungan yang signifikan pada seluruh variabel penelitian (p≥0,05). Kesimpulan dari penelitian ini menunjukkan bahwa tidak adanya hubungan antara tingkat kecukupan karbohidrat, tingkat kecukupan protein, tingkat kecukupan lemak, status gizi dan aktivitas fisik terhadap kebugaran atlet (p ≥ 0,05). Tidak ada hubungan yang bermakna antara tingkat kecukupan zat gizi makro, status gizi dan aktivitas fisik terhadap kebugaran atlet bulutangkis.